Chronic Stress Effects on Tumor: Pathway and Mechanism - Hong, Hanqing; Ji, Min; Lai, Dongmei (Frontiers in Oncology, 2021)
Abstract Chronic stress is an emotional experience that occurs when people encounter something they cannot adapt to. Repeated chronic stress increases the risk of a variety of diseases, such as cardiovascular disease, depression, endocrine disease, inflammation and cancer. A growing body of research has shown that there is a link between chronic stress and tumour occurrence in both animal studies and clinical studies. Chronic stress activates the neuroendocrine system (hypothalamic-pituitary-adrenal axis) and sympathetic nervous system. Stress hormones promote the occurrence and development of tumours through various mechanisms. In addition, chronic stress also affects the immune function of the body, leading to the decline of immune monitoring ability and promote the occurrence of tumours. The mechanisms of chronic stress leading to tumour include inflammation, autophagy and epigenetics. These factors increase the proliferation and invasion capacity of tumour cells and alter the tumour microenvironment. Antagonists targeting adrenergic receptors have played a beneficial role in improving antitumour activity, as well as chemotherapy resistance and radiation resistance. Here, we review how these mechanisms contribute to tumour initiation and progression, and discuss whether these molecular mechanisms might be an ideal target to treat tumour.